Dry season distribution of land crabs, Gecarcinus quadratus (Crustacea: Gecarcinidae), in Corcovado National Park, Costa Rica - E. Griffiths, Megan (2007)
The land crab Gecarcinus quadratus is an engineering species that controls nutrient cycling in tropical forests. Factors regulating their coastal distribution are not fully understood. We quantified land crab distribution during the dry season at Sirena Field Station in Corcovado National Park, Costa Rica, and found that land crab burrow density decreases with increasing distance from the ocean. Leaf litter depth and tree seedling density are negatively correlated with land crab burrow density. Burrows are strongly associated with sand substrate and burrow density is comparatively low in clay substrate. Results suggest that G. quadratus is limited to a narrow coastal zone with sand substrate, and this distribution could have profound effects on plant community structure.